2016
DOI: 10.5433/1679-0359.2016v37n4p2067
|View full text |Cite
|
Sign up to set email alerts
|

Tifton 85 grass responses to different nitrogen levels and cutting intervals

Abstract: The objective of this study was to evaluate the influence of five levels of N and two regrowth intervals on the structural, productive, and nutritional characteristics of Tifton 85 grass (Cynodon spp). The experiment was conducted in a hay production field at the State University of West Paraná, planted in 2004 with Cynodon spp. cv. Tifton 85. The experiment was established in a randomized block design with factorial treatments of five N fertilization amounts (0, 25, 50, 75 and 100 kg ha -1 cut -1 ) applied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
1
6
0
11
Order By: Relevance
“…The presence of nitrogen positively influenced the TFP and LSP in the cycles (Fig 5.c, (Quaresma et al, 2011;Gomes et al, 2015b;Taffarel et al, 2016;Sanches et al, 2017). Sanches et al (2017) and Quaresma et al (2011) In relation to the SW doses applied in Tifton 85 grass ( Fig 4A), other authors have also observed the occurrence of increasing linear behaviour in dry matter yield.…”
Section: Yield Parameters Of Forage Dry Mattermentioning
confidence: 74%
See 3 more Smart Citations
“…The presence of nitrogen positively influenced the TFP and LSP in the cycles (Fig 5.c, (Quaresma et al, 2011;Gomes et al, 2015b;Taffarel et al, 2016;Sanches et al, 2017). Sanches et al (2017) and Quaresma et al (2011) In relation to the SW doses applied in Tifton 85 grass ( Fig 4A), other authors have also observed the occurrence of increasing linear behaviour in dry matter yield.…”
Section: Yield Parameters Of Forage Dry Mattermentioning
confidence: 74%
“…Higher values observed in this work (33.6 and 31.7% in the lowest and the highest dose respectively), is possibly due to higher dose of SW adopted in this experiment. Taffarel et al (2016) and Sanches et al (2017), studied different nitrogen doses (0, 25, 50, 75 and 100 kg ha -1 and 25, 50, 75 and 100 kg ha -1 , respectively) but did not observe any effect with respect to relation to the cycle. It is understood that the nutritional responses are smaller and less evident than those of dry matter accumulation.…”
Section: Bromatological Parameters: Nutritive Value Of Foragementioning
confidence: 88%
See 2 more Smart Citations
“…Ipean) (Fagundes et al, 2005), Marandu palisadegrass under continuous stocking (Mesquita et al, 2010) and rotational stocking (Gimenes et al, 2011;Costa et al, 2016). Taffarel et al (2016) observed that the N fertilization increased dry matter production because altered the structural characteristics of the plants, such as a higher canopy, longer stems, higher leaf elongation. Costa et al (2016) founded that topdressing N fertilization in Marandu palisadegrass increases dry matter production and N-accumulation in plant tissues.…”
Section: The Importance Of Nitrogen In Pasturesmentioning
confidence: 99%